Free Energy Calculation of CO2 in Cholinium-Based Amino Acid Ionic Liquids - Salehin, F.N. (Springer Science and Business Media B.V., 2021)
Solvation free energy of CO2 in six cholinium based ionic liquids (ILs) was predicted by using Bennet Acceptance Ratio (BAR) method employed in molecular dynamics (MD) simulation. From solvation free energy, the degree removal of acid gases can be measured by gas solubility in liquids and quantified by excess chemical potential (Î¼ex) and Henryâs law constant (kH). In this work, the predicted solvation free energies of CO2 in six ChlAA ILs showed the highest value of kH was 78.89Â atm obtained by ChlSRI and the lowest value gained by ChlMEH was 45.35Â atm. Radial distribution function (RDF) for specific atom of CO2 and pure ILs was evaluated to assess our understanding on the interaction between the gas and the ILs. There were several characteristics that affected the solubility of CO2 in these six cholinium-based ILs such as the type of amines, functional group, free volume of ILs, and length of alkyl chain of anions. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.